Eksplorasi Perceived Ease of Use (PEOU), Perceived Usefulness (PU), dan Trust terhadap adopsi fintech di Riau dengan menggunakan perspektif Consumer Culture Theory (CCT) - Afrizal Malik; Syafaruddin Z; septian wahyudi (Pelantar Press, 2025)
This study explores the influence of Perceived Ease of Use (PEOU), Perceived Usefulness (PU), and Trust on fintech adoption in Riau using the Consumer Culture Theory (CCT) perspective. The findings indicate that PEOU has a significant impact on fintech adoption, with a regression coefficient of 0.837, a standard error of 0.040, a t-value of 21.185, and a significance of 0.000 (p 0.05). This suggests that the easier a fintech system is to use, the more likely it is to be adopted by the public in Riau. Additionally, PU also significantly influences fintech adoption, with a regression coefficient of 0.101, a standard error of 0.028, a t-value of 3.641, and a significance of 0.000 (p 0.05). This finding highlights consumers are more inclined to adopt fintech if they perceive tangible benefits such as transaction efficiency and broader financial access. However, Trust does not significantly impact fintech adoption, as indicated by a regression coefficient of 0.013, a standard error of 0.015, a t-value of 0.883, and a significance of 0.379 (p 0.05). This suggests that fintech users in Riau prioritize functionality and ease of use over trust when deciding to adopt financial technology services. The simultaneous analysis confirms that PEOU, PU, and Trust collectively influence fintech adoption, with an F-value of 5837.754 and a significance of 0.000 (p 0.05). Moreover, the Adjusted R Square value of 0.993 indicates that the model explains 99.3% of the variance in fintech adoption. These findings align with the CCT perspective, emphasizing that fintech adoption in Riau is driven more by pragmatic factors such as ease of use and perceived benefits rather than trust-related concerns